Telegram from Fridel Halstead addressed to Georg Bredig, November 22, 1939 - Halstead, Fridel G. (1939)
Telegram from Fridel Halstead to Georg Bredig (1868-1944), providing an address.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Boschwitz, Karl; Merzbach, George; Telegraph; Chemists; Halstead, Fridel G.